2015
DOI: 10.1177/0145445515573986
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Interventions to Reduce Multiply Controlled Vocal Stereotypy

Abstract: This study examined four interventions targeted at decreasing multiply controlled vocal stereotypy for a 12-year-old boy diagnosed with autism spectrum disorder and a severe intellectual disability. These interventions included Noncontingent Music, Differential Reinforcement of Other Behaviors, Self-Recording, and Functional Communication Training (FCT). In addition to measuring vocal stereotypy during each condition, task engagement and challenging behavior were also monitored. Across conditions, vocal stereo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…These positive effects are further increased when skill‐based reinforcement thinning procedures are added to FCT, for example demand fading (e.g., Berg et al, 2007) or contingency‐based delay tolerance training (e.g., Ghaemmaghami et al, 2016), which may be due to the explicit efforts to strengthen other contextually appropriate responses in addition to communication. Regarding collateral reductions, Wacker et al (1998) reported a decrease in other minor topographies of problem behavior not directly treated by FCT and Scalzo et al (2015) showed that FCT resulted in increased task engagement and lower levels of nontargeted challenging behavior. These effects may not be transient; Berg et al (2007) showed the secondary effects of FCT on social interactions and task completion in both training and generalization contexts across settings and people.…”
Section: Resultsmentioning
confidence: 99%
“…These positive effects are further increased when skill‐based reinforcement thinning procedures are added to FCT, for example demand fading (e.g., Berg et al, 2007) or contingency‐based delay tolerance training (e.g., Ghaemmaghami et al, 2016), which may be due to the explicit efforts to strengthen other contextually appropriate responses in addition to communication. Regarding collateral reductions, Wacker et al (1998) reported a decrease in other minor topographies of problem behavior not directly treated by FCT and Scalzo et al (2015) showed that FCT resulted in increased task engagement and lower levels of nontargeted challenging behavior. These effects may not be transient; Berg et al (2007) showed the secondary effects of FCT on social interactions and task completion in both training and generalization contexts across settings and people.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, instructors in the current study exposed Harry and Aiden to their ongoing academic acquisition (nonmastered) tasks, whereas Lanovaz and colleagues (2012, 2014) used mastered activities. Nevertheless, the results for Jeremy and Sam show that continuous music is not universally effective for treating vocal stereotypy during either leisure or demand contexts (see also Scalzo et al, 2015). To this end, Rapp, Brogan, and Cook (2018) noted that even though some studies have found that continuous auditory stimulation decreases vocal stereotypy, others have shown that continuous music actually increases vocal or motor stereotypy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research on stereotypy treatments have generally focused on children in controlled settings and studies have not examined reducing stereotypy in adults with ASD (Lanovaz & Sladeczek, 2012). Additionally, our study extends this area of research by moving beyond evaluations in highly structured settings (Colon & Ahearn, 2019; Scalzo et al, 2015; Taylor et al, 2005). Our intervention was successfully evaluated across multiple community‐based settings at a large public university.…”
Section: Discussionmentioning
confidence: 60%
“…Scalzo et al (2015) also compared intervention strategies for decreasing vocal stereotypy for a 12‐year‐old child with ASD. They compared noncontingent music, a DRO procedure, self‐recording, and FCT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation